382. Incidence of Hospital-Acquired and Ventilator-Associated Pneumonia in Patients with Severe COVID 19 on High Flow Oxygen. (31st December 2020) - Papamanoli, Aikaterini; Nakamura, Jacquelyn; Fung, Jenny; Abata, Joshua; Karkala, Nikitha; Tsui, Stella T; Yoo, Jeanwoo; Grewal, Prabhjot; Mojahedi, Azad; Dhaliwal, Simrat; Jacob, Robin; Hotelling, Jessica; et al.
Abstract: Background: Hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) can be serious complications of coronavirus disease 19 (COVID-19). Co-infections may worsen outcomes and prolong hospitalization. This risk may be exacerbated by systemic corticosteroids (steroids) and other adjunctive therapies. Methods: We reviewed the records of all adults admitted to Stony Brook University Hospital, NY, from 3/1 to 4/15, 2020 with severe COVID-19 pneumonia, requiring high-ﬂow O2 (non-rebreather mask, Venturi mask with FiO2 >50%, or high-ﬂow nasal cannula). We excluded patients who received mechanical ventilation (MV) or died within 24h. Patients were followed until death or hospital discharge. We reviewed positive sputum cultures (PSC) for pathogenic microorganisms and calculated the incidence of HAP and VAP (nosocomial pneumonia, [NP]), rates of MV and impact on mortality. Fungi isolated from sputum, were considered colonization unless associated with fungemia. We also examined the impact of adjunctive therapies with immunosuppressive potential (steroids and tocilizumab), on HAP or VAP. Results: A total of 469 patients were included (Table 1 ). Of these, 199 (42.4%) required intensive care and 172 (36.7%) MV. Median length of stay was 13 days (8–22) and 105 (22.4%) had PSC. Of these, 59 were considered true pathogens (HAP: 11, VAP: 48), with predominance of S. aureus (MSSA) 38.9%, Enterobacteriaceae 33.8% and Pseudomonas species 18.6%. 39 isolates were considered colonization (Table 2); Patients with PSC < 48h (N=7) from admission, were not considered NP. The incidence of NP was 7.0 per 1000 patient-days (95%CI 5.5–8.5). Of 11 patients with HAP, 9 needed MV. NP was more frequent among patients receiving steroids (9.0 vs 5.7 per 1000 patient-days; P=0.023). Use of tocilizumab was not associated with NP (6.2 vs 8.4 per 1000 patient-days; P=0.11). Mortality was nonsignificantly higher in patients with (20/59, 33.9%) vs. without (103/410, 25.1%) NP (P=0.16). Intubation and length of stay were the strongest predictors of NP in multivariable models. Cohort Characteristics of Patients with Severe COVID -19 Pneumonia on High Flow Oxygen (N= 469) All Microbes Isolated from Sputum Cultures Conclusion: Among high risk COVID-19 patients, NP is a common complication. MSSA and Enterobacteriaceae were the most frequent isolates. The risk increases with intubation, longer hospital stay and use of steroids but not tocilizumab. Disclosures: All Authors : No reported disclosures